Impact of pre-graft serology on risk of BKPyV infection post-renal transplantation. Issue 4 (29th September 2021) - François, Catherine; Tinez, Claire; Brochot, Etienne; Duverlie, Gilles; Castelain, Sandrine; Helle, François; Fiore, Toni; Morel, Virginie; Touzé, Antoine; Sater, Fadi Abdel; Dakroub, Fatima; Akl, Haidar; et al.
ABSTRACT: Objectives: BK polyomavirus-associated nephropathy is a troublesome disease caused by BK polyomavirus (BKPyV) infection in immunocompromised renal graft recipients. There are no effective treatments available, making immunosuppression reduction the only management option. Thus, pre-graft predictive BKPyV replication markers are needed for identification of patients at high risk of viraemia. Methods: We conducted a retrospective study to assess the correlation between pre-transplantation BKPyV serostatus and post-transplantation incidence of BKPyV infection. Sera from 329 recipients and 222 matched donors were tested for anti-BKPyV antibodies against BKPyV serotypes I and IV by using a virus-like particle-based immunoglobulin G enzyme-linked immunosorbent assay, and BKPyV DNA load was monitored for at least 1 year post-transplantation. Results: Eighty recipients were viruric and 59 recipients were viraemic post-transplantation. In the post-transplantation period, the probability of developing viraemia for serotype I increased from 4.3% for the D−/R+ group to 12.1% for the D+/R+ group, climbing to 37.5% for the D+/R− group (P < 0.05). When calculating recipient mean titres for serotypes I and IV, we observed a clear difference in the proportions of viraemia, decreasing from 50% for mean titres <400 to 13.5% for titres ≥400 (P < 0.001), as well as a higher proportion of presumptive nephropathy (50% versus 23.1%, respectively; P < 0.05). In univariate analysis, this parameter had an odds ratio of 6.41 for the risk of developing post-transplantation BKPyV viraemia (95% confidence interval 3.16–13.07; P < 0.0001). Conclusions: Determination of both donor and recipient BKPyV seropositivity before transplantation and antibody titre measurements may serve as a predictive tool to manage clinical BKPyV infection by identification of patients at high risk.